Assessment of Arable Farmers’ Response to the Impact of Urbanisation in Ilorin Metropolis, Kwara State, Nigeria (e-Proceedings of the Faculty of Agriculture International Conference, 2025)
Expansion of urban areas, causing demand for more residential, commercial, and industrial spaces, poses profound impacts on rural farming community land that feeds the populace. Urbanization not only reduces the amount of land available for food production but also leads to fragmentation of agricultural landscapes, making farming activities more challenging. This study sought to assess the response of arable farmers to the impacts of urbanization in Ilorin Metropolis, Kwara State, Nigeria. A three-stage sampling procedure was used in selecting one hundred and sixty-seven respondents for the study. Data were obtained using a structured questionnaire and was analyzed through frequencies, percentages, means, standard deviation and chi-square. The result revealed that majority of the respondents were males (73.7%), married (87.4%) and with an average age of about 56.7 years. About half (59.1%) of the respondents indicated awareness of urban farming techniques. Diversification into livestock production (x̄=1.67) and engaging in non-farming activities (x̄ =1.55) were the major responses of the farmers to the impacts of urbanization. The results also revealed that age, primary occupation and household size have a significant relationship with the farmers’ responses to the impacts of urbanization at p